Air Pollution in Micro-Environments: A Case Study of India Habitat Centre Enclosed Vehicular Parking, New Delhi. Issue 4 (August 2013) - Samal, Choudhury Gyanranjan; Gupta, Divya; Pathania, Rohit; Mohan, S.; Suresh, R.
Indoor air pollution deteriorates the quality of air present in the household or enclosed areas. The polluted air present contains hazardous pollutants like carbon monoxide (CO), nitrogen oxides, volatile organic compounds and particulate matter which could be respired easily. When inhaled, these pollutants can cause negative health impacts leading to various pulmonary and cardiac problems and in extreme conditions to mortality. Enclosed parking garages are one of the major sources for indoor air pollution. The reason for buildup of combustion pollutants is a lack of proper ventilation system in enclosed parking areas. Therefore, proper planning is required during construction design rather than post-construction addition of this necessary facility. In this study, the micro-environment of India Habitat Centre (IHC) parking area and their pollutants concentrations was examined; the pollutants concentrations were compared with ambient air concentrations. The pollutants found were in higher concentrations than the ambient; e.g., CO level ranged from 12 ppm to a maximum level of 164 ppm, exceeding the American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE) and WHO guidelines; similarly PM2.5 concentration averaged more than 100 µg·m –3 with a maximum concentration of 234 µg·m –3 and NO2 concentration were 25 to 56 µg·m –3, thereby leading to indoor air pollution and main sufferers are the guards and employees of IHC. Mitigation measures have been suggested for ameliorating the problem.